(3GdLGeY GdUZjQs - (3eMeO Hf GdMSf Hf aQbO GdTjHGfj (B( (3ehdGge (B) (3, CHh YHO Gddg , J (B189 (3g` s ((3eMeO GdLedi s)
(3ChdgG (B:s
(3jHOC HHGH GdeSJMGVI s
(3BNQgG (B:s
(3jfJgi HHGH UjO GdHGRi s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B561s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfajs